Safety analysis of acyclovir use in neonates based on the FDA Adverse Event Reporting System - Longbing He; Bo Wang; Yang Wang; Youshuai Chen (Medicine, 2026)
Acyclovir is the first-line treatment for neonatal herpes simplex virus infection; however, safety evidence in neonates remains limited. This study aimed to evaluate the safety profile of acyclovir in neonates using real-world pharmacovigilance data from the Food and Drug Administration Adverse Event Reporting System. This retrospective observational study analyzed adverse event (AE) reports in neonates (≤28 days) in which acyclovir was identified as the primary suspected drug in the Food and Drug Administration Adverse Event Reporting System from 2004 to Q3 2024. Disproportionality analyses were performed using the reporting odds ratio (ROR), proportional reporting ratio (PRR), Bayesian confidence propagation neural network, and empirical Bayesian geometric mean (EBGM). Positive risk signals were defined as those meeting the statistical significance criteria across all 4 methods. A total of 130 reports comprising 409 AEs were identified. Four system organ classes showed positive risk signals: skin and subcutaneous tissue disorders (ROR = 6.22, PRR = 5.88, lower limit of 95% confidence interval [CI] of the information component [IC025] = 1.98, lower limit of 95% CI of EBGM [EBGM05] = 4.16), general disorders and administration site conditions (ROR = 4.27, PRR = 3.47, IC025 = 1.47, EBGM05 = 2.85), hepatobiliary disorders (ROR = 3.85, PRR = 3.74, IC025 = 1.19, EBGM05 = 2.43), and renal and urinary disorders (ROR = 3.84, PRR = 3.70, IC025 = 1.24, EBGM05 = 2.51). At the preferred term level, 12 positive signals were detected, with the strongest signals observed for infusion site necrosis/edema (ROR = 939.92, 95% CI: 97.56–9055.25), arthritis (ROR = 179.47, 95% CI: 52.33–615.44), skin exfoliation/necrosis (ROR = 131.18, 95% CI: 46.00–374.06), and Kawasaki disease (ROR = 114.20, 95% CI: 36.21–360.15). Notably, Kawasaki disease, rectal hemorrhage, and necrotizing colitis were not described in existing product labeling. Acyclovir use in neonates may be associated with immune, gastrointestinal, hepatic, and renal AEs, underscoring the need for careful clinical monitoring. Further prospective studies are warranted to validate these associations.